Features Of The Development Of The Tourist Services Market In Uzbekistan - Toyirova Sarvinoz Atoevna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This article analyzes the scientific basis for the development of tourism services in Uzbekistan, the role of tourism products in tourism, as well as the opening of a tourism enterprise to introduce it in the tourism business of Uzbekistan, the introduction of new tourism products and the Uzbek domestic tourism market. improvement proposals have been developed